The Influence of Transformational Leadership and Intrapreneurship Behavior on Innovative Work Behavior in the Business Support Directorate of TIC (Testing, Inspection, Consultation) Companies in Indonesia - Syifa Ammalia; Pantius Drahen Soeling (Green Publisher Indonesia, 2024)
This study explores the influence of transformational leadership and intrapreneurship behavior on innovative work behavior within the Business Support Directorate of a TIC (Testing, Inspection, Consultation) company in Indonesia. The organization is undergoing a significant transformation in response to rapid global changes and the need for innovation. Through a quantitative explanatory research approach, data was collected from permanent employees using a total population sampling method. Multiple linear regression analysis revealed that both transformational leadership and intrapreneurship behavior positively influence innovative work behavior. In particular, intrapreneurship behavior exhibited a stronger impact. The study highlights the importance of fostering leadership and intrapreneurial qualities to drive innovation and maintain a competitive edge in the TIC industry. The findings offer practical recommendations to enhance organizational innovation, employee engagement, and adaptability for sustainable business success.